Training on business capital management for UMKM "Talaga Biru" Making Dangke (made from cow's milk) in Enrekang district: Working Capital Planning and Management Strategies. - Utami, Dwi; Wahyu Ramadhani, Magfirah (Outline Journal of Community Development, 2025)
The purpose of this activity is to increase the capacity of MSME actors in managing their businesses professionally. The PKM partner is the "Talaga Biru" MSME in Enrekang Regency which is engaged in the production of dangkemade from cow's milk. The problem faced by the partner is the lack of understanding in planning and managing working capital, which has an impact on the operational efficiency of the business. The method used is participatory training through theory sessions, discussions, and simulations. The results achieved are an increase in the knowledge and skills of business actors in preparing capital needs plans and working capital management strategies, which are expected to be able to support the sustainability and development of the business in a more focused manner.